Jawahir Al-Bukhari of Tuan Haji Husayn : a significance hadith text in social teaching - Latifah Abdul Majid (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2010)
This article presents an investigation into the part played by Tuan Husayn in disseminating Hadith teaching in Malay world. It is concerned primarily with the use of specific Hadith text (Jawahir al-Bukhari) as a tool for social teaching in Malaysia. It is an attempt to provide a briefly work on the subject, particularly the role of this text in terms of his transmission of fundamental Islamic principles to Malay Muslims. In the interests of validity and reliability, the study provides multiple sources of evidence. These include tape-recorded indepth interviews1 with researchers (in particular with an expert educationalist in twentieth century social, political and religious affairs in Malaysia) and academicians who are biographers of Husayn identified. My approach to the text builds also on the employments of the interpretation approach used in the understanding of text. Thus, research methods used to examine the original writings of Husayn are largely ‘qualitative2, and consist of approaches such as ‘hermeneutics’ and the ‘inferential’ technique of content analysis. This article identifies that in social and religious discourse in Malaysia the use of Hadith texts serves social and political as well as religious practical teaching. It also identifies that the development of the Hadith in Malaysia and its significance for Malay Muslims was signified by several issues raised by Malay religious scholars. This includes the consciousness and critique of Malay Muslims on the misconduct in their lives. Among the purposes of the translation and commentary of Arabic texts are the definitions of an ideal Islamic society and to preserve the Hadith of the Prophet s.a.w to the Malay community. Such discourse is an example of an increasingly common genre of Malay Islamic literature that emphasizes the ‘unity’ and ‘brotherhood’ of the Muslim community.